2010
DOI: 10.1007/s11698-010-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Do technological booms matter? New evidence on the relationship between firm size and innovativeness

Abstract: Many papers have been written about the effect of firm size on innovativeness, revealing a positive, a negative or a mixed impact. To this day, the so-called Schumpeterian hypothesis of the above-average innovativeness of large firms has neither been confirmed nor rejected, often because of insufficient data or a too-short observation period. Many studies concentrate only on a specific region or sector, or they analyze a very short time period. Windows of technological opportunities, providing technological bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…In either case, there should be a positive relationship between size and (successful) technological innovation. However, the empirical evidence for such a relationship between size (or the d egree of industry concentration) on one hand and innovativeness or R&D intensity on the other is often contradictory or ambiguous (Degner, 2011;Dolfsma and van der Velde, 2014). More specifically, with regard to the subject of technology strategy and its relationship to internal factors such as size and resources of the firm, Pavitt (1990:24) concluded that this strategy is "determined largely by the firm's size and the nature of its accumulated technological competences."…”
Section: Internal Factors Of Innovation Strategiesmentioning
confidence: 99%
“…In either case, there should be a positive relationship between size and (successful) technological innovation. However, the empirical evidence for such a relationship between size (or the d egree of industry concentration) on one hand and innovativeness or R&D intensity on the other is often contradictory or ambiguous (Degner, 2011;Dolfsma and van der Velde, 2014). More specifically, with regard to the subject of technology strategy and its relationship to internal factors such as size and resources of the firm, Pavitt (1990:24) concluded that this strategy is "determined largely by the firm's size and the nature of its accumulated technological competences."…”
Section: Internal Factors Of Innovation Strategiesmentioning
confidence: 99%
“…Yenilikçiliği etkileyen çok sayıda faktörün olması ve farklı ülkelerde farklı endüstri kollarında benzer sonuçların elde edilmemesi, bu konuda bir fikir birliğinin oluşmadığını göstermektedir. Bugüne kadar Schumpeter'in hipotezi, ne tam olarak doğrulanmış ne de reddedilmiştir (Degner, 2011). Ancak genel inanış, KOBİ'lerin yenilikteki payının 1945'den beri yükselmekte olduğudur (Oakey vd., 1988).…”
Section: Fi̇rma Büyüklüğü Ve Yeni̇li̇kunclassified
“…Firma büyüklüğünün yenilikçilik üzerindeki pozitif, negatif veya karma etkileri üzerine birçok örnek bulunmaktadır (Degner, 2011). Ekonomik İşbirliği ve Kalkınma Teşkilatı'nın (OECD) 30 ülkede yaptığı araştırmaya göre KOBİ'ler, Ar-Ge payları her geçen gün artmasına rağmen yenilik bakımından halen büyük firmaların oldukça gerisindedirler (OECD, 2005).…”
Section: Fi̇rma Büyüklüğü Ve Yeni̇li̇kunclassified
“…TFP approximates technological change as the residual of the growth equation.6 For an extensive discussion on the determinants of technology in the Schumpeterian tradition, seeDegne (2011).7 Of course, a typical drawback, is that R&D expenses of a firm can capture only the input size and do not provide any information regarding the output side (Kleinknecht 2001).8 For an extensive discussion on patents seeGriliches (2008),Degne and Streb (2010).…”
mentioning
confidence: 99%